De la Configuración Corporal a la Masculinidad en Militares (2019)
The present research work has as object of study the social representation of masculinity in amputees soldiers because of their work activity. This corresponds to a study that is framed in a qualitative design with exploratory scope which epistemically allows to locate it in the comprehensive interpretive field. As a data collection technique, a semi-structured interview was used, which was administered to 5 soldiers wounded in acts of service and who have in common the amputation of a part of their body.